Intracerebroventricular oxytocin administration in rats enhances object recognition and increases expression of neurotrophins, microtubule‐associated protein 2, and synapsin I. Issue 6 (22nd January 2015) - Havranek, Tomas; Zatkova, Martina; Lestanova, Zuzana; Bacova, Zuzana; Mravec, Boris; Hodosy, Julius; Strbak, Vladimir; Bakos, Jan
Abstract : Brain oxytocin regulates a variety of social and affiliative behaviors and affects also learning and memory. However, mechanisms of its action at the level of neuronal circuits are not fully understood. The present study tests the hypothesis that molecular factors required for memory formation and synaptic plasticity, including brain‐derived neurotrophic factor, neural growth factor, nestin, microtubule‐associated protein 2 (MAP2), and synapsin I, are enhanced by central administration of oxytocin. We also investigated whether oxytocin enhances object recognition and acts as anxiolytic agent. Therefore, male Wistar rats were infused continuously with oxytocin (20 ng/µl) via an osmotic minipump into the lateral cerebral ventricle for 7 days; controls were infused with vehicle. The object recognition test, open field test, and elevated plus maze test were performed on the sixth, seventh, and eighth days from starting the infusion. No significant effects of oxytocin on anxious‐like behavior were observed. The object recognition test showed that oxytocin‐treated rats significantly preferred unknown objects. Oxytocin treatment significantly increased gene expression and protein levels of neurotrophins, MAP2, and synapsin I in the hippocampus. No changes were observed in nestin expression. Our results provide the first direct evidence implicating oxytocin as a regulator of brain plasticity at the level of changes of neuronal growth factors, cytoskeletal proteins, and behavior. The data support assumption that oxytocin is important for short‐term hippocampus‐dependent memory. © 2015 Wiley Periodicals, Inc.